(untitled) (Anclajes, 2025)
Paying attention to the singular construction of the slave Andrés in the story “El angel caído” (1862) by Juana Manuela Gorriti, published in La Revista de Lima and included three years later in Sueños y realidades (1865), allows us to notice that this subaltern subject is configured as threatening based on the elements that associate him, as anticipated in the title of the narrative, with evil and more particularly with the figure of Satan or Lucifer. It is proposed that Gorriti appropriates the satanic attributes exalted by the romantics to invest the slave and take advantage, in a relocation that intertwines with political, historical, and sexual contextual meanings, of the implications that this demonic figure, codified in literary terms, carries. The analysis will show that this does not respond to a demonizing logic, but to a complex effect of empathy and rejection, identification and repudiation.